(untitled) (Research, Society and Development, 2025)
Introduction: Desloratadine, an efficient histamine H1 receptor antagonist, is widely used in the treatment of allergic reactions, acting as an antihistamine and anti-inflammatory agent. In addition to its anti-inflammatory properties, some studies have shown positive effects of this drug in inhibiting carcinogenesis pathways, which, added to the scarce literature on its biological effects on cancer cells, makes it a target of studies. Objective: Assess the toxicity and carcinogenic potential of the antihistamine Desloratadine. Methodology: Analyzes were performed using the test for detection of epithelial tumor clones (ETT) in somatic cells of Drosophila melanogaster. Thus, third instar larvae of D. melanogaster, descendants of the cross between wts/TM3 and multiple wing hair (mwh/mwh) strains, were submitted to a treatment with four concentrations of Desloratadine (1.56, 3.125, 6.25, and 12.50 mg/mL), and a negative control (osmosis reverse water) and a positive control (doxorubicin) were also included. Results: Desloratadine alone did not promote a significant increase (p>0.05) in the frequency of mutant spots. Conclusion: Under the present experimental conditions, Desloratadinedid not show a carcinogenic effect.